2011
DOI: 10.1523/jneurosci.4308-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitinase ABC Combined with Neurotrophin NT-3 Secretion and NR2D Expression Promotes Axonal Plasticity and Functional Recovery in Rats with Lateral Hemisection of the Spinal Cord

Abstract: Elevating spinal levels of neurotrophin NT-3 (NT3) while increasing expression of the NR2D subunit of the NMDA receptor using a HSV viral construct promotes formation of novel multisynaptic projections from lateral white matter (LWM) axons to motoneurons in neonates. However, this treatment is ineffective after postnatal day 10. Because chondroitinase ABC (ChABC) treatment restores plasticity in the adult CNS, we have added ChABC to this treatment and applied the combination to adult rats receiving a left late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 55 publications
5
61
0
Order By: Relevance
“…Neurotrophin NT3 is an essential factor required for growth of new connections and has been implicated to enhance regenerative sprouting and reorganization of damaged fibers in the injured spinal cord (Alto et al 2009;Schnell et al 1994;Tuszynski and Gage 1995). Electrophysiological experiments, however, revealed that NT3 may enhance plasticity at synaptic inputs to lumbar motoneurons in neonates (Arvanian et al 2003) but not in damaged spinal cord of adult rats when applied alone (García-Alías et al 2011;Schnell et al 2011). Consistent with these results, chronic administration of NT3 alone via AAV vectors had only limited effects on locomotion in transected animals, although the combination of NT3 with cutaneous stimulation was able to induce plantar stepping in paraplegic rats (Boyce et al 2012).…”
Section: Aav-nt3 Treatment Combined With Sems and Exercise Induced Fusupporting
confidence: 52%
See 1 more Smart Citation
“…Neurotrophin NT3 is an essential factor required for growth of new connections and has been implicated to enhance regenerative sprouting and reorganization of damaged fibers in the injured spinal cord (Alto et al 2009;Schnell et al 1994;Tuszynski and Gage 1995). Electrophysiological experiments, however, revealed that NT3 may enhance plasticity at synaptic inputs to lumbar motoneurons in neonates (Arvanian et al 2003) but not in damaged spinal cord of adult rats when applied alone (García-Alías et al 2011;Schnell et al 2011). Consistent with these results, chronic administration of NT3 alone via AAV vectors had only limited effects on locomotion in transected animals, although the combination of NT3 with cutaneous stimulation was able to induce plantar stepping in paraplegic rats (Boyce et al 2012).…”
Section: Aav-nt3 Treatment Combined With Sems and Exercise Induced Fusupporting
confidence: 52%
“…Our earlier electrophysiological studies revealed that synaptic connections from lateral white matter (LWM) to individual motoneurons could be strengthened by administration of neurotrophin 3 (NT3) using engineered fibroblast implantation (Arvanian et al 2003). This action of NT3, however, required the reversal of the developmental loss of neuronal N-methyl-D-aspartate (NMDA) receptor activity at these synaptic inputs, which we achieved through herpes simplex virus 1 vector-mediated overexpression of the juvenile form of NMDA receptors (Arvanian et al 2004;García-Alías et al 2011;.…”
mentioning
confidence: 99%
“…The most axonal sprouting and best behavioral recovery in the BBB locomotor test was seen in the full combination group, and electrical conductivity across the lesion was only reestablished in rats receiving the combination. This treatment did not cause hypersensitivity in any group [31,32] .…”
Section: Chabc and N-methyl-d-aspartate (Nmda) Receptor Typementioning
confidence: 74%
“…it is therefore important to study the treatment effects of regenerative treatments in combination with rehabilitation. ChABC opens a window of plasticity and has proven effective when specific rehabilitation is given during the period of drug administration, in both acute and delayed stages and up to one year post-injury in two SCi models [16,31] .…”
Section: Combination Of Regenerative Treatments With Rehabilitationmentioning
confidence: 99%
“…The injection of ChABC in the visual cortex and in the amygdala has been shown to reactivate juvenile forms of experience-dependent plasticity in adult rodents 12,13 . Similarly, the injection of ChABC in the damaged rat spinal cord was also found to improve synaptic plasticity after spinal cord injury 20 .…”
mentioning
confidence: 92%